Análisis del impacto de la tecnología en las microempresas de Puerto Colombia. (2021)
When carrying out the analysis of the impact of 4.0 technologies in the companies of Puerto Colombia (Atlantic), we are beginning to understand that the high costs of technology Currently, they are not attractive to microentrepreneurs, who are not willing to accept this help to improve your business; assuming all goes well and your decision is continue working under the traditional model, which is wrong, because they are still stuck as companies with the tendency to disappear. On the other hand, with the identification and use of these tools, they can exercise more control over all business processes, demonstrates the importance of adapting as a company to existing new technologies, understanding that it is not complicated, on the contrary, it leads them to a universe of benefits, among these, increased productivity, improves the relationship with customers, the administration of work teams, improvements in communication and collaboration of resources through technological platforms, among many more benefits